2008
DOI: 10.1002/gps.2058
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hip fracture, heart failure and weight loss on the risk of institutionalization of community‐dwelling patients with dementia

Abstract: This study confirms the independent contribution of specific medical symptoms and diseases to earlier institutionalization of patients with dementia. These results stress the importance of better knowledge of the specific characteristics of hip fracture, weight loss and congestive heart failure in the context of dementia, to make more effective prevention possible in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…These estimates are in accordance with previous studies showing a 2-3-fold increase in hip fracture risk among AD patients [1], [4], [6][8], [10][15], [21].…”
Section: Discussionsupporting
confidence: 93%
“…These estimates are in accordance with previous studies showing a 2-3-fold increase in hip fracture risk among AD patients [1], [4], [6][8], [10][15], [21].…”
Section: Discussionsupporting
confidence: 93%
“…1). Other studies have found that, in addition to dementia, physical illness is an important predictor of institutionalization, too [91,92]. As the caregiver's health may change both due to caregiving and independently of it, it should be assigned not only to caregiving-related aspects, as it is done in the original model.…”
Section: Discussionmentioning
confidence: 99%
“…One study 50 found that the presence of fracture in the three years before the diagnosis of dementia, the existence of acute congestive heart failure episodes and a body weight loss of over 5% over one year, were independently associated with the institutionalization of patients with dementia.…”
Section: Functional Recoverymentioning
confidence: 97%